2016
DOI: 10.1159/000446694
|View full text |Cite
|
Sign up to set email alerts
|

Small Cell Carcinoma of the Ovary (Hypercalcemic Type): Malignant Rhabdoid Tumor

Abstract: We present a rare case of malignant rhabdoid tumor (ovarian small cell carcinoma of hypercalcemic type) in a 24-year-old female with fulminant course. Clinically, hypercalcemia was not found at the time of primary diagnosis. However, it appeared later during the course of tumor progression. Histologically, the tumor showed classical features of small cell carcinoma of hypercalcemic type. Therapy included radical surgery with adjuvant chemotherapy. Despite this intensive therapy, the disease recurred and the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…Small cell carcinoma of the ovary of hypercalcemic type (SCCOHT) is a very rare tumor usually found in young females [17]. Hypercalcemia is found in most cases, and is associated with a poor prognosis [127,128]. In almost all SCCOHT tumors, inactivating mutations leading to loss of BRG1/ SMARCA4 expression have been exclusively found [129], and mutations of this protein were observed in 91% of cases [125,126].…”
Section: Resultsmentioning
confidence: 99%
“…Small cell carcinoma of the ovary of hypercalcemic type (SCCOHT) is a very rare tumor usually found in young females [17]. Hypercalcemia is found in most cases, and is associated with a poor prognosis [127,128]. In almost all SCCOHT tumors, inactivating mutations leading to loss of BRG1/ SMARCA4 expression have been exclusively found [129], and mutations of this protein were observed in 91% of cases [125,126].…”
Section: Resultsmentioning
confidence: 99%
“…Ovarian cancers have been shown to be associated with HHM predominantly with clear cell subtype and small-cell carcinomas( Table 2 ) 9 . Clear cell carcinoma is characterized by the presence of clear cells, upon hematoxylin and eosin staining for rich cytoplasmic glycogen content, and high-grade nuclei with mitotic hyperactivity, which indicate the aggressive nature of this histological subtype.…”
Section: Discussionmentioning
confidence: 99%
“…In rare cases exhibiting rhabdoid cytomorphology, the tumor cells were very similar to malignant rhabdoid tumor(MRT) (14).Molecular genetic studies showed that small cell carcinoma (hypercalcemic type) contained alterations in genes SMARCB1 or SMARCA4 also observed in MRTs; therefore, some authors renamed it as 'MRT of the ovary' (15).…”
Section: Discussionmentioning
confidence: 99%